Healthy living: meaning for the homeless in Santa Maria - Leandra Porto; Dirce Stein Backes; Grassele Denardini Facin Diefenbach; Regina Gema Santini Costenaro; Rosiane Filipin Rangel; Dirce Beatriz Marquardt Lucio; Elenice Spagnolo Rodrigues Martins (Universidade Federal de Santa Maria, 2012)
Objective: to search meaning of healthy living for street dweller of Santa Maria, RS. Method: qualitative and explorative research. Results: twenty male individuals were interviewed, in the period of February to June of 2009. The participators were selected casually, with the one criterion of inclusion being street dweller, with or without temporary permanence in the hostel. Data were analyzed under the light of hermeneutic interpretation, because this referential allows understanding with profoundness the text, the discourse of the participators, when emerge three categories. Final considerations: while for same street dwellers to live in the street means liberty, for others the hostel means to abstain themselves of alcohol ingestion and of others illicit drugs, promoting so a healthy living